Neurovascular unit, neuroinflammation and neurodegeneration markers in brain disorders - Kempuraj, Duraisamy; Dourvetakis, Kirk D.; Cohen, Jessica; Valladares, Daniel Seth; Joshi, Rhitik Samir; Kothuru, Sai Puneeth; Anderson, Tristin; Chinnappan, Baskaran; Cheema, Amanpreet K.; Klimas, Nancy G.; Theoharides, Theoharis C. (Frontiers in Cellular Neuroscience, 2024)
Neurovascular unit inflammation via activation of glial cells and neuronal damage plays a critical role in neurodegenerative diseases. Though the exact mechanism of disease pathogenesis is not understood, certain biomarkers provide valuable insight into the disease pathogenesis, severity, progression and therapeutic efficacy. These markers can be used to assess pathophysiological status of brain cells including neurons, astrocytes, microglia, oligodendrocytes, specialized microvascular endothelial cells, pericytes, NVU, and blood-brain barrier (BBB) disruption.Damage or derangements in tight junction (TJ), adherens junction (AdJ), and gap junction (GJ) components of the BBB lead to increased permeability and neuroinflammation in various brain disorders including neurodegenerative disorders. Thus, neuroinflammatory markers can be evaluated in blood, cerebrospinal fluid (CSF), or brain tissues to determine neurological disease severity, progression, and therapeutic responsiveness. Recent BBB-on-a-chip modeling offers promising potential for providing an in-depth understanding of brain disorders and neurotherapeutics. Chronic inflammation is common in age-related neurodegenerative disorders including Alzheimer's disease (AD), Parkinson's disease (PD), and dementia.Neurotrauma/traumatic brain injury (TBI) also leads to cute chronic neuroinflammatory responses.The expression of some markers may also be altered many years or even decades before the onset of neurodegenerative disorders. In this review, we discuss markers of neuroinflammation, and neurodegeneration associated with acute and chronic brain disorders, especially those associated with neurovascular pathologies. These biomarkers can be evaluated in CSF, or brain tissues and include neurofilament light (NfL), ubiquitin C-terminal hydrolase-L1 (UCHL1), glial fibrillary acidic protein (GFAP), Ionized calcium-binding adaptor molecule 1 (Iba-1), transmembrane protein 119 (TMEM119), aquaporin, endothelin-1, and platelet-derived growth factor receptor beta (PDGFRβ) are some important neuroinflammatory markers. Recent BBB-on-a-chip modeling offers promising potential for providing an in-depth understanding of brain disorders and neurotherapeutics. Integration of these markers in clinical practice could potentially enhance early diagnosis, monitor disease progression, and improve therapeutic outcomes.